2017
DOI: 10.1039/c7ta07573a
|View full text |Cite
|
Sign up to set email alerts
|

MOF derived ZnCo2O4 porous hollow spheres functionalized with Ag nanoparticles for a long-cycle and high-capacity lithium ion battery anode

Abstract: Ag nanoparticle-decorated ZnCo2O4 hollow spheres are synthesized by using MOF templates and an Ag-mirror reaction, for high-performance lithium-ion battery anode materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…[23] Fu et al showed that an ovel porous spherical ZnO@carbon nanocomposite obtained throughp yrolyzing the corresponding ZnO@ZIF-8 could get ah igh surface area and stable cycling performance. [28] Multi-metal oxidesh ave been reported as anode materials for LIBsi nm any previous literatures, such as FeTiO 3 , [29] ZnCo 2 O 4 , [30,31] ZnFe 2 O 4 , [32] etc. They are attractive due to their high specific capacities andt he synergetice ffects between the two conversion metal elements during the discharge/charge process.…”
Section: Introductionmentioning
confidence: 95%
“…[23] Fu et al showed that an ovel porous spherical ZnO@carbon nanocomposite obtained throughp yrolyzing the corresponding ZnO@ZIF-8 could get ah igh surface area and stable cycling performance. [28] Multi-metal oxidesh ave been reported as anode materials for LIBsi nm any previous literatures, such as FeTiO 3 , [29] ZnCo 2 O 4 , [30,31] ZnFe 2 O 4 , [32] etc. They are attractive due to their high specific capacities andt he synergetice ffects between the two conversion metal elements during the discharge/charge process.…”
Section: Introductionmentioning
confidence: 95%
“…Among them, ZnCo 2 O 4 combines the better anodic performance of cobalt-based oxides and the lower cost/toxicity of Zn. What is more, compared with other ACo 2 O 4 (where A = Ni, Fe, Cu, and Mg), ZnCo 2 O 4 has higher theoretical specific capacity as not only can Zn–O and Co–O host lithium ions through conversion reaction, but the alloy of Zn–Li also forms during electrochemical reactions [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Based on these considerations, many ZnCo 2 O 4 -based materials with different nanostructures have been synthesized and studied as the anode materials for lithium ion batteries, for example, ZnCo 2 O 4 hollow nanobarrels [ 17 ], ZnCo 2 O 4 nanoclusters [ 18 ], ultrathin ZnCo 2 O 4 nanosheets [ 14 ], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, many ZnCo 2 O 4 -based materials with different nanostructures have been synthesized and studied as the anode materials for lithium ion batteries, for example, ZnCo 2 O 4 hollow nanobarrels [ 17 ], ZnCo 2 O 4 nanoclusters [ 18 ], ultrathin ZnCo 2 O 4 nanosheets [ 14 ], and so on. By constructing these different structures, the volume change during cycling can be greatly restrained; the pathway for electron and Li + diffusion can be decreased; and, thus, both rate and cycling performance can be greatly enhanced compared with the bulk materials [ 11 , 13 , 15 , 16 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…have been emerged as the advanced anode materials due to their rich redox chemistry and high theoretical capacity, as compared with the state-ofthe-art graphite. [19][20][21] In particular, cobalt sulfides (CoS) is one of the most prospective anode materials for LIBs. Nevertheless, cobalt-based sulfides suffer from the poor intrinsic conductivity, which limits their rate capability.…”
Section: Introductionmentioning
confidence: 99%